Morbimortalidad en trauma ortopédico de alta energía: estudio descriptivo retrospectivo (2018)
ABSTRACT: To describe the mortality and the main secondary complications in patients with high-energy orthopedic trauma treated at the emergency service of the Hospital Universitario San Vicente Fundación. Methodology: descriptive retrospective study carried out in an 18-month period with patients following the inclusion criteria and after a search conducted in the hospital’s database. 10,259 patient medical records were reviewed, out of which 161 followed the inclusion criteria. The quantitative variables were analyzed by standard means and deviations. The qualitative variables were analyzed by frequency and proportions. Results: most of the affected patients were males (80.7%), with a mean age of 37.5 years, the most affected bone was the tibia (68.3). Transit accident was the main mechanism of trauma (82%), and the most frequently involved vehicle was the motorcycle (65.8%). There was a low mortality of three patients. The main complications were chronic osteomyelitis and pulmonary thromboembolism (7.4% and 6.8%, respectively). Sixteen patients needed attention in the Intensive Care Unit (9.9%), remaining there for an average of 6.9 days. Conclusions: high-energy orthopedic trauma is not an independent mortality factor. However, it affects public health by generating medical leaves of active workers, which causes work absences and diminishes productivity.